SPE Annual Technical Conference and Exhibition 2013
DOI: 10.2118/166242-ms
|View full text |Cite
|
Sign up to set email alerts
|

Eagle Ford Completion Optimization Using Horizontal Log Data

Abstract: Schlumberger and four Eagle Ford Shale Play operators drilling in South Texas joined a consortium initiative to acquire various types of open hole logging data in several horizontal wells, and use the data to design the completions with optimum fracture stage and perforation cluster positioning. Horizontal production logs were subsequently used to gauge the effectiveness of using the log data to engineer the completions. This paper outlines the data acquisition techniques, analyses made on that data, applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…In fact, if anything there is a disconnect between stress shadow modeling and the available data; to the authors' knowledge none of the published PLT data for multistage, multi-entry-point hydraulic fracturing of horizontal wells (e.g. Cipolla et al, 2011;Slocombe et al, 2013) shows any evidence of intrastage patterns of production that would be consistent with stress shadow impacts. Whats more, the existing PLT data is only rarely, and then partially, presented along with enough information for the reader to group perforation clusters into stages in order to look for patterns of production that may or may not be consistent with the prediction of stress shadow models.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…In fact, if anything there is a disconnect between stress shadow modeling and the available data; to the authors' knowledge none of the published PLT data for multistage, multi-entry-point hydraulic fracturing of horizontal wells (e.g. Cipolla et al, 2011;Slocombe et al, 2013) shows any evidence of intrastage patterns of production that would be consistent with stress shadow impacts. Whats more, the existing PLT data is only rarely, and then partially, presented along with enough information for the reader to group perforation clusters into stages in order to look for patterns of production that may or may not be consistent with the prediction of stress shadow models.…”
Section: Introductionmentioning
confidence: 91%
“…Baihly et al, 2010). This approach has been shown to decrease the percentage of non-producing clusters from ∼36% to ∼18% in Eagle Ford wells (Slocombe et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…There are various explanations to this including not initiating hydraulic fractures, insufficient proppant placement, or loss of near-wellbore connection due to over flushing or severe drawdown. One likely cause is hydraulic fractures not initiating in a few perforation clusters due to variation of rock properties along the lateral when placed geometrically (Slocombe et al, 2013). This study uses observations and data presented by Slocombe et al (2013) to create the distribution of stress along the lateral.…”
Section: Example 1: Single-well Padmentioning
confidence: 99%
“…In this case, it is recommended to keep good distance for perforation clusters away from major faults or potential water connectors in the reservoirs. Slocombe et al (2013) indicated that about 36% of the perforated clusters are not effective in the Eagle Ford. That paper outlines a methodology of using log data obtained in horizontal wells for improving stimulation efficiency and enhancing productivity.…”
Section: Avoiding Water Problemmentioning
confidence: 99%
“…However, this may not necessarily result in the most optimal completion design. In a recent study, it was reported that about 1/3 of the perforated clusters on average were not flowing as measured by production logs (Slocombe et al, 2013, Fisher et al, 2004. Obviously the non-effective perforation clusters are a big portion of the total stimulation cost.…”
Section: Introductionmentioning
confidence: 99%